House of Commons : manuel of procedure in the public business laid on the Table by Mr. Speaker for the use of members. (London : His Majesty's Stationery Office, 1942)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: politieke instellingen; Groot-Brittannië.